A model student: The road to further education. (2nd October 2019) - Hancock, David
Abstract : Emma Wallace completed the transition from midwife to full-time health visitor and went on to undertake a Master's degree. Here she talks about her experience of part-time study and the opportunities it has presented to develop her career